A discourse analysis Of tourism advertisements In english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Language of advertising is a very special communicative form in society with customers through given products or service in which language has its own characteristics that make it different from the other languages. Therefore, the thesis aims at analyzing, comparing and contrasting the differences and similarities of discourse features in tourism advertisements in English and Vietnamese in terms of layout, lexical choice, cohesive and stylistic devices. The findings show that English tourism advertisements (ETAds) display a general layout with three parts: Overview, Tour Details and Additional Mentions. Lexical devices show triggering words, adjectives, adverbs, pronouns and nouns are prominent lexical features which were thoroughly analyzed and compared. Besides, reference, ellipsis, conjuction, repetition and general words in both English and Vietnamese tourism advertisements (VTAds) are also exploited in cohesive devices. Finally, stylistic analysis reveals simile, metaphor, rhetorical questions and hyperbole in ETAds and simile, metaphor and hyperbole in VTAds, these are the prominent devices used in both ETAds and VTAds. Based on the findings, the thesis gave out some implications and suggestions for teaching and learning in both languages. This paper is significant in providing some linguistic and pedagogical contributions, especially for those who work for tourism or travel agencies in promoting their trade name as well as their products. It is hoped that the result of the thesis is really useful documentation to those who are interested in tourism advertisements.